2013
DOI: 10.17795/compreped-8423
|View full text |Cite
|
Sign up to set email alerts
|

Lower Gastrointestinal Bleeding in Children: Experiences From Referral Center in Southern Iran

Abstract: Background: Lower gastrointestinal bleeding (LGIB) in infants and children is a common problem in medical centers; however, its epidemiologic properties have not been studied well. Objectives: Due to the fact that LGIB has various causes in different geographical places, considering the importance of etiology in decision making for diagnostic techniques and treatment and since the lack of comprehensive database related to this issue, the main purpose of the current study was to determine the main causes of LGI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Polyps were more common in <5 years age group (48.1%) than other pathology and that was statistically significant. Begum et al 23 & Alam et al 35 from Bangladesh, Deeb et al 28 from Egypt and Moravej et al 36 from Iran also found the similar results.…”
Section: Discussionsupporting
confidence: 56%
“…Polyps were more common in <5 years age group (48.1%) than other pathology and that was statistically significant. Begum et al 23 & Alam et al 35 from Bangladesh, Deeb et al 28 from Egypt and Moravej et al 36 from Iran also found the similar results.…”
Section: Discussionsupporting
confidence: 56%
“…Our finding (7%) is in close agreement with previous studies showing similar proportions of patients with LGIB being subsequently diagnosed as IBD by Panda et al (6.5%) 19 and Moravej et al (6.47%). 15 We did not encounter lymphoid nodular hyperplasia (NLH) as a cause of LGIB as described by Panda et al 19 NLH is a vague entity and often an incidental finding in colonoscopy and encountered more in children in the first decade. The highly variable prevalence of NLH is often attributed to underreporting in colonoscopy.…”
Section: Discussionmentioning
confidence: 73%
“…Normal colonoscopy was found in a variable proportion of patients in different studies. 12 14 15 Normal colonoscopy could be attributed to several etiologies including lesion hidden behind mucosal folds, etiology in the small bowel that resolved by itself, and missed lesions due to poor preparation or ulcers that healed itself before the procedure was performed. These lacunae can be addressed by relook procedures in case of recurrence of overt or occult GI bleed being subjected to relook colonoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IBD is a commonly encountered disease in patients with lower GI bleeding. In an Iranian study, IBD was detected in 20 (6.5%) of 309 children with rectal bleeding (15). The mean age of Iranian patients with IBD was 10.3 years in another Iranian study (16).…”
Section: Discussionmentioning
confidence: 95%